2020
DOI: 10.9734/jeai/2020/v42i130451
|View full text |Cite
|
Sign up to set email alerts
|

Study on Rice Residue Management Options on Growth Parameters and Growth Indices of Rice Crop

Abstract: The research was conducted to study the effect of management options for combine harvested rice residue and its effect on succeeding rice crop growth responses. The experiment was laid out in field using a randomized block design with nine treatments and replicated three times. The computed biometric data were subjected to statistical scrutiny.  Incorporation of combine harvested rice residue with 25 kg additional N ha-1 as basal + bio-mineralizer (2 kg t-1 of rice residue) and cow dung slurry (5%) recorded hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This could be attributed to more number of taller plants, tillers and higher drymatter production per unit area and LAI. These findings are in accordance with Kumar et al (2016) and Vijayaprabhakar et al (2020).…”
Section: Resultssupporting
confidence: 93%
“…This could be attributed to more number of taller plants, tillers and higher drymatter production per unit area and LAI. These findings are in accordance with Kumar et al (2016) and Vijayaprabhakar et al (2020).…”
Section: Resultssupporting
confidence: 93%
“…The enhanced uptake of these nutrients might have resulted in increased vegetative growth of plant. In parallel, Vijayaprabhakar et al [10] reported that the incorporation of harvested rice residue with 25 kg additional N ha -1 as basal + bio-mineralizer (2 kg t -1 of rice residue) and cow dung slurry (5 %) recorded higher plant height and number of tillers hill -1 over incorporation of straw alone and removal of straw.…”
Section: Growth Attributes Of Paddymentioning
confidence: 99%
“…With the increase of nitrogen levels, grain and straw yield, plant height, productive tillers filled spikelet per panicles, SLA, CGR increase. In long term production practices, farmers have found that paddy straw incorporation can indeed improve rice yield and there are significant differences in the effect of rice straw incorporation on rice growth, yield and quality (Vijayaprabhakar et al 2020).With exploding population and rapid depletion and degradation of natural resources, it is necessary to save the natural resources, and to use them efficiently. Recycling of crop residues is an essential component in achieving sustainability.…”
Section: Introductionmentioning
confidence: 99%